The Difference Giving Formula Milk and Breast Milk Exclusive Against Nutritional Status of Babeis with Ages 3- 7 Month - Noni Fidya Ayu Anandasari; Fariha Nuzulul Hinisa (Universitas Nurul Jadid Paiton Probolinggo, East Java, Indonesia, 67291, 2025)
Good nutrition is paramount, especially in babies, a state of good nutrition is very influential to improve the process of growth and development in children. Good nutrition can be obtained from good nutrition Similarly, breast milk is an ideal baby food, with a balanced composition and in accordance with the needs of the baby's growth. The purpose of this study was founded out how the nutritional status of babeis fed formula milk and babies are given exclusive breastfeeding, and to investigate differences in nutritional status between babeis fed formula with babeis given breast milk exclusively. The research design comparative descriptive with cross sectional approach. The population used were 3- 7 month old babies in the Dinoyo Public Health Center, Lowokwaru District, Malang City. with due regard to inclusion and exclusion criteria as many as 40 infants. Having more nutrition by Mann Whitney test values obtained with a Z count equal -2.102 P- value 0.036 < α (0.05), it can be concluded that there is a significant difference in formula feeding and exclusive breastfeeding on nutritional status in babes with aged 3- 7 months in Dinoyo Public Health Center, Lowokwaru District, Malang City. The health worker is expected to be counseling and promoting the health benefits of exclusive breastfeeding (example: posters, pamphlets, and counseling to mothers) to increase the use of breast milk in Indonesia, so that pressing the incidence of malnutrition status or more.